2(5H)-Furanone sesquiterpenes from Eremophila bignoniiflora: High-resolution inhibition profiling and PTP1B inhibitory activity. (October 2019) - Zhao, Yong; Kjaerulff, Louise; Kongstad, Kenneth T.; Heskes, Allison M.; Møller, Birger Lindberg; Staerk, Dan
Abstract: Eremophila bignoniiflora is a shrub distributed throughout inland northern and eastern Australia, and it has been used in several medicinal applications by some Australian Aboriginal people. In our continued search for anti-diabetic constituents from natural resources, the crude ethyl acetate extract of E. bignoniiflora was found to have protein-tyrosine phosphatase 1B (PTP1B) inhibitory activity with an IC50 value of 23.9 ± 1.9 μg/mL. High-resolution PTP1B inhibition profiling combined with HRMS and NMR were subsequently used to investigate the individual compounds responsible for the observed bioactivity of the crude extract. This led to identification of five undescribed 2(5 H )-furanone sesquiterpenes, together with 13 flavonoids and phenolic compounds. Dose-response curves of the isolated compounds revealed that two 2(5 H )-furanone sesquiterpene cinnamates and three flavonoids exhibited moderate PTP1B inhibitory activity with IC50 values from 41.4 ± 1.4 to 154.5 ± 8.9 μM. Graphical abstract: 2(5 H )-furanone sesquiterpene cinnamates and flavonoids from Eremophila bignoniiflora identified as moderate proteine-tyrosine phosphatase 1B inhibitors.Image 1 Highlights: Ethyl acetate extract of Eremophila bignoniiflora showed PTP1B inhibitory activity. High-resolution PTP1B inhibition profiling was used to pinpoint bioactive compounds. Five 2(5 H )-furanone sesquiterpenes were isolated and structurally characterized. Two 2(5 H )-furanosesquiterpene cinnamates exhibited moderate PTP1B inhibition.